Study of Sangihe-Filipino fishermen activity in Bitung City, North Sulawesi, Indonesia - Thamin, Aswan; Manoppo, Victoria N; Mantiri, Desy M.H (AQUATIC SCIENCE & MANAGEMENT, 2013)
The study was conducted in the coastal area of Lembeh Strait, Bitung City, North Sulawesi, Indonesia. Seven districts comprised the test site. The aim of this research was to analyze the activity of fishermen of Sangihe-Filipino descent (Sa-Fi) by multiple regression analysis. Primary data concerning fishing activities of Sa-Fi Fishermen was obtained through interview techniques, questionnaires and field observation. Activity values ​​(Y) show a factor of fishing activities (Xn) which allegedly affect the fishermen activities. These results indicated that the activity of Sa - Fi fishermen affected by the language that they use in carrying out life as a fisherman in Bitung City. Old fishermen settled in Bitung correlated with fishing knowledge. Sa-Fi fishermen fishing knowledge correlated with the number of dependents and income of fishermen families. Sa-Fi fishermen's income is correlated with their spending. Penelitian dilakukan di wilayah pesisir Selat Lembeh Kota Bitung pada 7 kecamatan sebagai lokasi penelitian, untuk menganalisis aktivitas nelayan keturunan Sangihe-Filipina (Sa-Fi) dengan analisis regresi berganda. Data primer mengenai aktivitas nelayan Sa-Fi diperoleh melalui teknik wawancara, penyebaran kuesioner dan observasi lapangan. Nilai aktivitas (Y) menunjukkan faktor kegiatan penangkapan ikan (Xn) yang diduga berpengaruh terhadap aktivitas nelayan. Hasil penelitian ini menunjukkan bahwa aktivitas nelayan Sa-Fi dipengaruhi oleh bahasa yang mereka gunakan dalam menjalankan kehidupannya sebagai nelayan di Kota Bitung. Lama menetap nelayan Sa-Fi di Kota Bitung berkorelasi dengan pengetahuan menangkap ikan. Pengetahuan menangkap ikan nelayan Sa-Fi berkorelasi dengan jumlah tanggungan keluarga dan pendapatan nelayan. Pendapatan nelayan Sa-Fi berkorelasi dengan pengeluaran nelayan.